1999
DOI: 10.1007/s11627-999-0081-2
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious shoot regeneration from Sinningia speciosa leaf discs in vitro and stability of ploidy level in subcultures

Abstract: Leaf explants of SinningLa speciosa were cultured in vitro on Murashige and Skoog (MS) basal medium with various growth substances in order to regenerate shoots. On MS medium supplemented with indoleacetic acid (IAA) and kinetin, 80% of the explants produced green callus and 25 to 30 shoots with roots per explant. On MS supplemented with IAA and N 6 benzyladenine (BA), 80% of the explants produced green callus and 40 to 50 shoots per explaut but lacked roots. After 3-4 mo., these shoots were removed from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the family Gesneriaceae, adventitious shoot regeneration from leaf discs and in vitro propagation in Sinningia spp. have been reported (Scaramuzzi et al 1999, Nhut et al 2005. Somatic embryogenesis and rapid multiplication in vitro has been reported in Chirita longgangensis (Tang et al 2007).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 96%
“…In the family Gesneriaceae, adventitious shoot regeneration from leaf discs and in vitro propagation in Sinningia spp. have been reported (Scaramuzzi et al 1999, Nhut et al 2005. Somatic embryogenesis and rapid multiplication in vitro has been reported in Chirita longgangensis (Tang et al 2007).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 96%
“…Previous studies have reported that leaf explants of S. speciosa initially form callus and adventitious buds in media containing BA and NAA, with subsequent roots produced on medium supplemented with NAA alone; moreover, the regenerated rates did not exceed 91.5% (Scaramuzzi et al 1999; Zhou et al 2000 ;Cao and Wang 2002). Most protocols report use of 0.3-4.0 mg l −1 BA with 0.01-0.2 mg l −1 NAA to induce calli, followed by a transfer to new medium containing 2.0 mg l −1 BA with 0.01-0.2 mg l −1 NAA to induce shoot differentiation (Scaramuzzi et al 1999;Zhou et al 2000;Cao and Wang 2002). These methods require two or more steps to obtain regenerated plants.…”
Section: Discussionmentioning
confidence: 93%
“…It is commonly known as gloxinia and is widely cultivated throughout the world as an ornamental horticulture crop due to its large, oval leaves and vibrantly colored, velvety, bell-shaped flowers (Sheehan and Tjia 1976;Scaramuzzi et al 1999;Nhut et al 2006;Brown 2007). However, it is difficult to obtain an abundance of healthy progeny, either by seed, due to self-sterility (Cao and Wang 2002), or by tubers (Scaramuzzi et al 1999). In vitro culture of plant organs or tissues have been accepted as an effective pathway to resolve this problem (Scaramuzzi et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations